2008
DOI: 10.1674/0003-0031(2008)159[162:auorrw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Avian Use of Rural Roadsides with Cattail (Typha spp.)

Abstract: ABSTRACT.-We surveyed 30 roadsides in North Dakota's Prairie Pothole Region for birds and active nests between May and July 2001-2002. Each roadside transect was 1608 m and had $200 linear meters of standing cattail (Typha spp.). We recorded 45 bird species; four species of Icteridae dominated the avifauna. Red-winged blackbirds (Agelaius phoeniceus) were both the most abundant species and most abundant nester, averaging 53 birds/10 ha (SE 5 7.7) and 30 nests/10 ha (SE 5 9.7). Among non-icterid species, song s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…According to the National Wetland Plants List of the US, species of Typha are considered obligate wetland plants, meaning they cannot survive in non-wetland habitats (Lichvar et al 2016). As such, Typha is found in a wide variety of wetland habitats including marshes, shores, streambanks, ditches, and margins of lakes and ponds, and tidal wetlands showing a tolerance for a range of water levels (Harris and Marshall 1963;Stewart and Kantrud 1972;Newman et al 1998;Safratowich et al 2008). Typha invasions into natural wetlands are often associated with hydrologic alterations.…”
Section: Hydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the National Wetland Plants List of the US, species of Typha are considered obligate wetland plants, meaning they cannot survive in non-wetland habitats (Lichvar et al 2016). As such, Typha is found in a wide variety of wetland habitats including marshes, shores, streambanks, ditches, and margins of lakes and ponds, and tidal wetlands showing a tolerance for a range of water levels (Harris and Marshall 1963;Stewart and Kantrud 1972;Newman et al 1998;Safratowich et al 2008). Typha invasions into natural wetlands are often associated with hydrologic alterations.…”
Section: Hydrologymentioning
confidence: 99%
“…The first collection of T. angustifolia was in 1942, and the first verified specimen of T. × glauca was in 1963. Since that time, Typha has become ubiquitous throughout the region (Stewart and Kantrud 1972;Kantrud 1986;Ralston et al 2007;Safratowich et al 2008;Post van der Burg et al 2014). Potholes have been associated with T. angustifolia and T. latifolia, and T. × glauca has become dominant in many areas Kantrud 1971, 1972;Kantrud 1986).…”
Section: Historical Presence and Current Extentmentioning
confidence: 99%
“…The higher abundance and frequency of occurrence of Red-winged Blackbird on roadside surveys is possibly because of a greater abundance of dense marsh vegetation around the relatively deep water bodies that form in ditches and livestock watering holes (Niemuth et al 2007, Safratowich et al 2008 in which this species nests, and near cropland (Yasukawa and Searcy 1995) in which it forages. Similar to the findings of other studies in the Canadian grasslands, we found that the Vesper Sparrow was more prevalent on roadside routes (Sutter et al 2000).…”
Section: Discussionmentioning
confidence: 99%